Evaluating Current Increased Price and Fattening Cost of Feeder Brahman Cross Cattle along with ESCAS Additional Cost on The Price of Slaughtered Cattle and Their Welfare - Puradireja, Rino Hadiwijaya; Daud, Andre Rivanda; Ramdani, Diky (Universitas Halu Oleo, 2023)
Australia's modern Brahman Cross (BX) cattle industry is based on animal welfare. The importation of BX cattle will be bound by the Exporter Supply Chain Assurance System (ESCAS) regulations. This study aimed to evaluate current increased price and fattening cost of feeder BX cattle along with ESCAS additional cost on the price of slaughtered cattle and their welfare. Based on the animal welfare assessment, while in the feedlot for 120 days were considered good, with the average value in the first month 86.4%, the second 88.5%, the third 92.14%, and the fourth 94.29%. Based on the calculations Activity Based Costing (ABC) method, it is known that procurement costs, including the purchase of feeders, contributed to 94% of the total costs, while other costs were handling costs 2.7%, cost of ESCAS 1.56%, selling cost 1.52%, and the lowest, maintenance cost 0.24%. Therefore, to fatten Australian BX cattle, special strategies are needed, such as: optimizing stock in the feedlot; efficiency cost in feed ingredients without reducing quality; applying animal welfare rules to minimize handling costs, and selecting vendors who want the lower price in providing ESCAS support facilities and establishing regular maintenance of the ESCAS supporting tools.